The Essential Elements of a Risk Governance Framework for Current and Future Nanotechnologies. Issue 7 (14th December 2017) - Stone, Vicki; Führ, Martin; Feindt, Peter H.; Bouwmeester, Hans; Linkov, Igor; Sabella, Stefania; Murphy, Finbarr; Bizer, Kilian; Tran, Lang; Ågerstrand, Marlene; Fito, Carlos; Andersen, Torben; et al.
Abstract: Societies worldwide are investing considerable resources into the safe development and use of nanomaterials. Although each of these protective efforts is crucial for governing the risks of nanomaterials, they are insufficient in isolation. What is missing is a more integrative governance approach that goes beyond legislation. Development of this approach must be evidence based and involve key stakeholders to ensure acceptance by end users. The challenge is to develop a framework that coordinates the variety of actors involved in nanotechnology and civil society to facilitate consideration of the complex issues that occur in this rapidly evolving research and development area. Here, we propose three sets of essential elements required to generate an effective risk governance framework for nanomaterials. (1) Advanced tools to facilitate risk‐based decision making, including an assessment of the needs of users regarding risk assessment, mitigation, and transfer. (2) An integrated model of predicted human behavior and decision making concerning nanomaterial risks. (3) Legal and other (nano‐specific and general) regulatory requirements to ensure compliance and to stimulate proactive approaches to safety. The implementation of such an approach should facilitate and motivate good practice for the various stakeholders to allow the safe and sustainable future development of nanotechnology.